En masse retraction versus two-step retraction of anterior teeth in extraction treatment of bimaxillary protrusion - Felemban, Nayef H. (Medknow Publications & Media Pvt Ltd, 2013)
In the present report, two techniques of space closure; two-step anterior teeth retraction (TSR) and en masse retraction (ER) were used in two adult patients who had bimaxillary protrusion and were treated with four premolar extractions and fixed orthodontic appliance therapy. Both patients had a Class I dental malocclusion and the same chief complaint, which is protrusive lips. Anterior teeth were retracted by two-step retraction; canine sliding followed by retraction of incisors with T-loop archwire in the first patient and by en masse retraction using Beta titanium alloy T-loop archwire in the second case. At the end of treatment, good balance and harmony of lips was achieved with maintenance of Class I relationships. The outcome of treatment was similar in the two patients with similar anchorage control. ER can be an acceptable alternative to the TSR during space closure since it is esthetically more acceptable. However, it requires accurate bending and positioning of the T-loop.